Transformational Leadership in the Digital Business Environment: A Systematic Literature Review of Innovation Capability, Management Accounting Systems, and Sustainable Firm Performance - Novrizal; Benardi (LPPM STIE Kasih Bangsa, 2026)
The rapid advancement of digital technologies has fundamentally transformed organizational leadership, innovation, and strategic management practices. This study conducts a qualitative Systematic Literature Review (SLR) to synthesize existing evidence on the relationships among transformational leadership, innovation capability, management accounting systems (MAS), and sustainable firm performance in the digital business environment. Following the PRISMA 2020 guidelines, peer reviewed articles published in internationally recognized journals were systematically identified, screened, and synthesized. The review reveals that transformational leadership contributes to sustainable firm performance primarily through strengthening innovation capability and promoting the strategic use of management accounting systems rather than through direct effects. Innovation capability enhances organizational adaptability, knowledge sharing, and value creation, while advanced MAS supports strategic decision making and organizational control. The findings further indicate that integrating transformational leadership, digital transformation, innovation capability, and strategic management accounting enables organizations to achieve long-term competitiveness and sustainability. This review provides theoretical insights and practical implications for future leadership and digital business research.